DERADIKALISASI MELALUI PENDIDIKAN KARAKTER BERBASIS KHAZANAH PESANTREN - Mifrohatul Musyarrofah (Jurnal Mudarrisuna: Media Kajian Pendidikan Agama Islam, 2018)
The current counter-terrorism effort has become a common commitment among the nations of the world. Conventionally, the effort to overcome terrorism is done through the approach of criminal law enforcement (penal). Some Muslims even argue that violence in the name of religion is including jihad in the Amar ma'ruf Nahi munkar and enforce the Islamic law as a whole (kaffah). The fact that most of the actors of radicalism and terrorism in the name of Islam in Indonesia are alumni of madrasah education or boarding school is inevitable. Nevertheless, to regard all types of educational institutions as a source of the teachings of radicalism and theorist is a fundamental mistake given the characteristics and patterns of developers of Islamic educational institutions in Indonesia are very diverse. Moreover, a number of findings indicate that Islamic educational institutions in Indonesia are very different compared to similar educational institutions in other countries. In the Islamic context, character education is to restore the divine values in humans (fitrah) with the guidance of the Qur'an and As-Sunnah so that become a man who akhlaqul karimah (insan kamil). Insan kamil is a perfect man in terms of manifestation and knowledge.